Practical comparisons among electronic energy meters, a precision energy meter and IEEE1459 for reactive energy measurements, under unbalanced and non-sinusoidal conditions - E Melo, G. A. [UNESP]; Fazio, A. [UNESP]; Sampaio, L. P. [UNESP]; De Brito, M. A. G. [UNESP]; Oliveira, R. A N [UNESP]; Canesin, C. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper presents a practical experimentation for comparing reactive/non-active energy measures, considering three-phase four-wire non-sinusoidal and unbalanced circuits, involving five different commercial electronic meters. The experimentation set provides separately voltage and current generation, each one with any waveform involving up to fifty-first harmonic components, identically compared with acquisitions obtained from utility. The experimental accuracy is guaranteed by a class A power analyzer, according to IEC61000-4-30 standard. Some current and voltage combination profiles are presented and confronted with two different references of reactive/non-active calculation methodologies; instantaneous power theory and IEEE 1459-2010. The first methodology considers the instantaneous power theory, present into the advanced mathematical internal algorithm from WT3000 power analyzer, and the second methodology, accomplish with IEEE 1459-2010 standard, uses waveform voltage and current acquisition from WT3000 as input data for a virtual meter developed on Mathlab/Simulink software. © 2012 IEEE.
Keywords: Class A; Commercial electronics; Current generation; Electronic energy meter; Energy measure; Energy meters; Harmonic components; IEEE 1459-2010; Input datas; Instantaneous power theory; Internal algorithms; Mathlab; Non-sinusoidal; Power analyzers; Practical experimentation; Three-phase four-wire; Unbalanced circuit; Wave forms; Experiments; Industrial applications; Electric measuring instruments